2016
DOI: 10.1021/acs.est.5b05207
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Kinetics of Contaminants Oxidation and the Generation of Manganese(III) in the Permanganate/Bisulfite Process

Abstract: Permanganate can be activated by bisulfite to generate soluble Mn(III) (noncomplexed with ligands other than H2O and OH(-)) which oxidizes organic contaminants at extraordinarily high rates. However, the generation of Mn(III) in the permanganate/bisulfite (PM/BS) process and the reactivity of Mn(III) toward emerging contaminants have never been quantified. In this work, Mn(III) generated in the PM/BS process was shown to absorb at 230-290 nm for the first time and disproportionated more easily at higher pH, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(41 citation statements)
references
References 48 publications
2
39
0
Order By: Relevance
“…The substrate oxidation can be represented in three steps, as it is a heterogeneous reaction. The substrate first adsorbs onto MnO 2 (equation 1 ), followed by oxidation by MnO 2 which was transformed to its reduced form MnOOH (equation 2 ), and then to aqueous Mn(II) (equation 3 ), and it is known that MnOOH is unstable and the reaction from MnOOH to Mn(II) is fast in the presence of substrate 27 , 28 . In the presence of oxygen, Mn(II) can be oxidized to MnOOH (equation 4 ) 19 , which appears to be rate limiting in the long run as discussed above.…”
Section: Resultsmentioning
confidence: 99%
“…The substrate oxidation can be represented in three steps, as it is a heterogeneous reaction. The substrate first adsorbs onto MnO 2 (equation 1 ), followed by oxidation by MnO 2 which was transformed to its reduced form MnOOH (equation 2 ), and then to aqueous Mn(II) (equation 3 ), and it is known that MnOOH is unstable and the reaction from MnOOH to Mn(II) is fast in the presence of substrate 27 , 28 . In the presence of oxygen, Mn(II) can be oxidized to MnOOH (equation 4 ) 19 , which appears to be rate limiting in the long run as discussed above.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Sun et al (2015Sun et al ( , 2016 reported a novel approach to yield the reactive Mn(III) species through the permanganate/ bisulfate (PM/BS) process. These reactive species could oxidize the organic contaminants at extraordinarily high rates.…”
Section: Introductionmentioning
confidence: 99%
“…). The presence of Mn(III) has been previously confirmed via pyrophosphate, and Mn(III) is able to rapidly remove organic compounds in tens of seconds[32][33][34]. The disproportion of Mn(III) could also generate Mn(IV) (Equation (11)).…”
mentioning
confidence: 84%
“…•− could be generated and play a significant role in organic compound oxidation in manganese-catalyzed sulfite activation processes, such as permanganate/sulfite, MnO 2 /sulfite, and Mn(II)/sulfite reactions [32][33][34]40 (Figure 7a). It was shown that, as solution pH increased, the produced MnO 2 was improved for both Mn(II)/sulfite and electro/Mn(II)/sulfite processes.…”
Section: Mechanism Studymentioning
confidence: 99%
See 1 more Smart Citation